Ski wax distribution at the surface of cross-country skis - Lefebvre, P.; Herody, J.; Charlot, F.; Coulmy, N.; Mantoux, A.; Coulmy, N.; Hagenmuller, P.; Blanquet, E. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: The International Ski and Snowboard federation (FIS) has banned fluorinated wax since winter 2023/2024 for health and environmental reasons [1]. Athletes must proceed to the inspection of their skis before each run to ensure no fluorine wax was used during the preparation. This control is currently done by infrared spectroscopy (FTIR) at three different points of the ski [2]. Very limited amount of wax can significantly improve the gliding performance [3]. One may thus wonder what the distribution of the wax onto the ski base is and what detection sensitivity should be attained for effective regulations?